A multicentre cohort study assessing day of week effect and outcome from emergency appendicectomy. Issue 9 (7th February 2014) - Ferguson, Henry JM; Hall, Nigel J; Bhangu, Aneel
Abstract : Background: There is evidence to suggest that patients undergoing treatment at weekends may be subject to different care processes and outcomes compared with weekdays. This study aimed to determine whether clinical outcomes from weekend appendicectomy are different from those performed on weekdays. Method: Multicentre cohort study during May–June 2012 from 95 centres (89 within the UK). The primary outcome was the 30-day adverse event rate. Multilevel modelling was used to account for clustering within hospitals while adjusting for case mix to produce adjusted ORs and 95% CIs. Results: When compared with Monday, there were no significant differences for other days of the week considering 30-day adverse events in adjusted models. On Sunday, rates of simple appendicitis were highest, and rates of normal (OR 0.62, 95% CI 0.42 to 0.90) and complex appendicitis (OR 0.65, 95% CI 0.46 to 0.93) lowest. This was accompanied by a 43% lower likelihood in use of laparoscopy on Sunday (OR 0.47, 95% CI 0.32 to 0.69), accompanied by the lowest level of consultant presence for the week. When pooling weekends and weekdays, laparoscopy use remained less likely at the weekend (OR 0.68, 95% CI 0.55 to 0.83), with no significant difference for 30-day adverse event rate (OR 1.01, 95% CI 0.80 to 1.29). Conclusions: This study found that weekend appendicectomy was not associated with increased 30-day adverse events. It cannot rule out smaller increases that may be shown by larger studies. It further illustrated that patients operated on at weekends were subject to different care processes, which may expose them to risk.